Use mathematical induction to prove the formula for all integers
n ≥ 1.
Let Sn be the equation 1 + 2 + 2^2 + 2^3 +... + 2^(n − 1) = (2^n) − 1
We will show that Sn is true for every integer n ≥ 1.
1 = (2^1 )− 1
The selected statement is true because both sides of the equation equal 1.
Show that for each integer k ≥ 1, if Sk is true, then Sk + 1 is true.
Assuming Sk is true, we have the following. (Simplify your answers completely.)
Sk = 1 + 2 + 22 + 23 +... +2^(k-1)=(2^k)-1
Then we have the following. (Simplify your answers completely.)
S_k + 1 = 1 + 2 + 22 + 23 +...+ 2k − 1 +__
= s_k+__
=(2^k)-